2021
DOI: 10.3390/ph14030187
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Drug-Related Problems and Complementary and Alternative Medicine Use in Malaysia: A Systematic Review and Meta-Analysis of 37,249 Older Adults

Abstract: Drug-related problems (DRPs) in the elderly include polypharmacy, potentially inappropriate medications, nonadherence, and drug-related falls. In this systematic review and meta-analysis, the prevalence of DRPs and complementary and alternative medicine (CAM) use among the Malaysian elderly was estimated. PubMed, Scopus, Web of Science, and Google Scholar databases were searched to identify studies published since their inception up to 24 August 2020. A random-effects model was used to generate the pooled prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 63 publications
1
31
1
1
Order By: Relevance
“…4,5 The percentage of patients experiencing DRPs is often near or above 50%. This has been found in many different countries, including Malaysia (50%), 6 the Netherlands (53%), 7 and Ethiopia (70%). 5 DRPs were more common in older patients and especially in people with chronic diseases.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…4,5 The percentage of patients experiencing DRPs is often near or above 50%. This has been found in many different countries, including Malaysia (50%), 6 the Netherlands (53%), 7 and Ethiopia (70%). 5 DRPs were more common in older patients and especially in people with chronic diseases.…”
Section: Introductionmentioning
confidence: 82%
“…For example, a study by Garin et al 35 found that 12% of patients experienced ADRs, but in our sample, only 5% of patients had ADRs. Basheti et al 36 found that 46.1% of outpatients with chronic diseases had nonadherence, and Chang et al 6 estimated that the pooled prevalence of nonadherence to medication was 60.6%. By contrast, in our study, 17.43% of patients experienced nonadherence.…”
Section: Science and Practicementioning
confidence: 99%
“…First, the included studies did not encompass all the states of the country, so the estimated prevalence might not fully represent the magnitude of drug-resistant TB in Sudan. Second, substantial heterogeneity was observed in the included studies, although this observation is common in meta-analyses on estimating prevalence [ 62 , 63 , 64 ]. Third, all of the included studies were hospital-based studies and none were community-based studies, making the results more susceptible to potential selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…A forest plot was generated to present the summarised results and heterogeneity among the included studies. Heterogeneity among studies was assessed using I 2 statistics, in which I 2 values of greater than 75% inidicated substantial heterogeneity [ 17 ]. The significance of heterogeneity was identified using Cochran’s Q-test.…”
Section: Methodsmentioning
confidence: 99%